EDUCATION BUDGET PLANNING STRATEGY IN REALIZING THE EFFECTIVENESS OF ELEMENTARY SCHOOL FINANCING IN KARAWANG REGENCY - Maman Suryaman; Acih Trisnawati; Titin Sutinah; Rizka Ummu Khoeriyah; Imas Mulyati; Devi Raswati; Sri Mulyani Munaeyza (RADJA PUBLIKA, 2025)
Educational budget planning has a strategic role in supporting the effectiveness and efficiency of financing in elementary schools. This study aims to examine the strategy of educational budget planning in improving the quality of financial management in five public elementary schools in Karawang Regency. The approach used is descriptive qualitative. Data collection techniques include in-depth interviews, participatory observation, and documentation studies. The results of the study indicate that budget preparation is carried out in a participatory manner, based on needs, and in line with the vision, mission, and School Work Plan (RKS). The principles of transparency, accountability, efficiency, and effectiveness are the main foundations in the budgeting process. Despite challenges such as late disbursement of funds and budget constraints, schools develop adaptive strategies through periodic evaluations, use of bridging funds, external collaboration, and utilization of information technology. These findings emphasize the importance of systematic and inclusive budget planning in realizing financial governance that supports the quality of elementary education.